2016
DOI: 10.1016/j.vetimm.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an inactivated genotype 2b porcine epidemic diarrhea virus vaccine in neonatal piglets

Abstract: Massive outbreaks of porcine epidemic diarrhea virus (PEDV) recurred in South Korea in 2013-2014 and affected approximately 40% of the swine breeding herds across the country, incurring a tremendous financial impact on producers and consumers. Despite the nationwide use of commercially available attenuated and inactivated vaccines in South Korea, PEDV has continued to plague the domestic pork industry, raising concerns regarding their protective efficacies and the need for new vaccine development. In a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 30 publications
0
37
1
Order By: Relevance
“…However, only inactivated/killed vaccines against G2b PEDV, which may be incapable of effectively controlling chronic PEDV enzootics, are commercially available in the domestic market. In our previous study, the double-dose immunization of pregnant sows with inactivated G2b vaccines conferred important passive protection to their litters (Baek et al, 2016). However, this study pointed out potential drawbacks of killed vaccines against PED in their effectiveness that does not fully mitigate mortality and morbidity rates of nursing piglets, probably owing to scant lactogenic immunity.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, only inactivated/killed vaccines against G2b PEDV, which may be incapable of effectively controlling chronic PEDV enzootics, are commercially available in the domestic market. In our previous study, the double-dose immunization of pregnant sows with inactivated G2b vaccines conferred important passive protection to their litters (Baek et al, 2016). However, this study pointed out potential drawbacks of killed vaccines against PED in their effectiveness that does not fully mitigate mortality and morbidity rates of nursing piglets, probably owing to scant lactogenic immunity.…”
Section: Introductionmentioning
confidence: 72%
“…The onset of PEDV fecal shedding in animals from the vaccinated sows was recorded at different times (3-7 dpc), and its termination varied among piglets, lasting up to 2 weeks after challenge. A recent study revealed that giving sows twice inactivated killed G2b vaccines (K/K vaccination) enhanced the survival rate of piglets against G2b challenge from 0% to 93% and relieved the severity and morbidity of diarrhea, including the fecal shedding of PEDV (Baek et al, 2016). Considering these results, the maternal L/K/K vaccinations applied in the present study were more efficacious than K/K treatment in terms of absolute improvement in survival rate and the significant mitigation of diarrheal severity, including the quantity and duration of viral shedding in stool.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to molecular evidence, antigenic variations between classical and emerging highly virulent (non-S INDEL) PEDV strains were demonstrated in several serological cross reactivity assays (Kim et al, 2015;Lin et al, 2015aLin et al, , 2015bWang et al, 2015). There are also some studies showed that the highly virulent (non-S INDEL) PEDV strains could provide piglets against homologous challenge (Baek et al, 2016;Lee et al, 2018;Lin et al, 2016b ;Park et al, 2018). Therefore, there is an urgent need for more research aimed at understanding the biological characteristics, pathogenicity, and immune protective effects of the field prevalent strain in the GII genogroup.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these are being assessed for their potential to mucosal immunity after oral administration. (Baek et al, 2016;Frederickson et al, 2014;Berube et al, 2015) Virions are inactivated with chemicals.…”
Section: Vaccines For Tgev and Other Coronavirusesmentioning
confidence: 99%
“…PEDV G2-b strains were responsible for recent severe PED epidemics in Asian countries and North America. Considering this fact, South Korean researchers (Baek et al, 2016) tested an inactivated vaccine based on serially cultured G2-b strain KOR/ KNU-141112/2014. Pregnant sows were immunized IM with the inactivated adjuvanted vaccine at 6 and 3 weeks prior to farrowing.…”
Section: Pedv Vaccines In Asiamentioning
confidence: 99%